A short measure of four types of personal optimism: ability, rivalry, chance, and social support (ARCS) - Diemo Urbig (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Self-efficacy, which can be defined as optimism about ones own ability to exercise required actions, has received a lot of attention in research on entrepreneurs and managers decision making. This attention led to the development of corresponding measurement instruments. However, there is no equivalent measure of the more general personal optimism that jointly captures on equivalent bases abilities and other sources of uncertainty, which one might be more or less optimistic about. I develop a measurement instrument of four dimensions of personal optimism: ability optimism (self-efficacy), rivalry optimism (being better than others), chance optimism (being a lucky devil or fearing of bad-luck), and social support optimism (others help and support me and are trustworthy). Correlations between subscales are intuitive and backed by theory. I replicate corresponding results from previous studies that used different measures, e.g. life-orientation (LOT-R), self-efficacy (NGSE), and social optimism at the societal level from the POSO scale. This new personal optimism measurement instrument is very much like the life-orientation test (LOT-R), but it provides more insights regarding the structure of optimism. Whenever self-efficacy or control beliefs are of interest, the ARCS or ACS scales should be used to control for complementary world beliefs. I also illustrate the special role of one item in NGSE, which in contrast to all other NGSE items refers to a comparative instead of an absolute judgment.
Keywords: 330; personal optimism; social optimism; chance optimism; self-efficacy; Meinung; Persönlichkeitspsychologie; Messung; Unternehmer